Garenoxacin as a prophylactic anti-infective in hydropneumothorax: a case study report - Haider, Shahid; Hajare, Anoop L.; Krishnaprasad, K.; Bhargava, Amit (International Journal of Basic & Clinical Pharmacology, 2017)
Pneumothorax appears to be a common clinical state. Iatrogenic pneumothorax occurs commonly after procedures such as transthoracic needle biopsy, pleural biopsy, positive pressure ventilation, etc. Diagnosis of iatrogenic pneumothorax is often delayed. Broad spectrum anti-infectives appear to be beneficial in reducing the infections, especially when chest drains are inserted. Garenoxacin, a potent quinolone with its unique structural modification appears to have an edge over other respiratory quinolones.